PENGARUH WORKSHOP ANTI PERUNDUNGAN TERHADAP KESIAPAN SISWA MENJADI DUTA ANTI PERUNDUNGAN DI SMK PUSAT KEUNGGULAN MANDIRI - Ali Daud Hasibuan (Universitas Negeri Medan, 2023)
The Effect of Anti-Bullying Workshops on Students' Readiness to Become Anti-Bullying Ambassadors at SMK Mandiri Excellence Centers. This study aims to determine the effect of anti-bullying workshops on students' readiness to become anti-bullying ambassadors at the Mandiri Excellence Center Vocational High School. The research sample is 40 people, taken in a porposive manner with the criteria; personality, department delegates, gender, and academic achievement. The research instrument used was a questionnaire about anti-bullying workshop activities and readiness to become anti-bullying ambassadors. Data were analyzed by data description and hypothesis testing. The results of data analysis show that; 1) The score of the anti-bullying workshop variable with a total score of 2,802, mean 70.05, median 70.00, mode 70, sd 5.54, variant 30, range 20, minimum score 60, and maximum score 80. Student readiness variable score to become anti-bullying ambassadors obtained a total of 2,945, mean 73.63, median 73.50, mode 70, sd 6,315, variant 39,881, range 28, minimum score 56, and maximum score 84. 2) Readiness of students to become anti-bullying ambassadors at school based on aspects of readiness 90.45%, readiness 87.99%, individual commitment 83.85%, and group commitment 87.29%. More specifically, psychological readiness of students is 90.36%, knowledge readiness is 89.43%, and technical readiness is 84.17%. 3) There is an effect of anti-bullying workshops on students' readiness to become anti-bullying ambassadors at school of 0.159 or 15.9% at a significance of 0.000.